A CRISIS OF THE ROMANISTIC TRADITION: PROSPECTS FOR THE HISTORIAGRPHY OF ROMAN LAW - Guandalini Jr, Walter (Iushistoria investigaciones, 2016)
This paper outlines a historical overview of western romanistic tradition, evaluating the meanings attributed to Classical Roman Law on the different periodsin which legal knowledge revitalized it. The article concludes by diagnosing the crisisfaced by romanistic tradition nowadays, suggesting its historical recovery as the onlyway out of it.